2007
DOI: 10.1021/es071041z
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Volatile Organic Compounds and Aldehydes in the U.S. Trucking Industry

Abstract: Diesel exhaust is a complex chemical mixture that has been linked to lung cancer mortality in a number of epidemiologic studies. However, the dose-response relationship remains largely undefined, and the specific components responsible for carcinogenicity have not been identified. Although previous focus has been on the particulate phase, diesel exhaust includes a vapor phase of numerous volatile organic compounds (VOCs) and aldehydes that are either known or suspected carcinogens, such as 1,3-butadiene, benze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Workers who are part of the transportation industry, such as drivers and service station workers, and individuals in occupation that are near traffic, such as police officers are exposed to levels of tens to hundreds of ppb [5255]. Peak values for mechanics who are exposed directly to gasoline fumes can approach ppm levels [5658].…”
Section: Methodologies For Measuring Benzene Exposurementioning
confidence: 99%
“…Workers who are part of the transportation industry, such as drivers and service station workers, and individuals in occupation that are near traffic, such as police officers are exposed to levels of tens to hundreds of ppb [5255]. Peak values for mechanics who are exposed directly to gasoline fumes can approach ppm levels [5658].…”
Section: Methodologies For Measuring Benzene Exposurementioning
confidence: 99%
“…Results on truck drivers and land transport sector are consistent with a study conducted in Finland on exposure to gasoline vapours (Vainiotalo and Ruonakangas 1999) that found a GM concentrations of benzene of 0.15-0.28 mg/m 3 (corresponding to about 0.05-0.09 ppm). A survey on occupational exposure to volatile organic compounds (VOCs) and aldehydes in the US trucking industry reported that driver exposures are a combination of car and truck emissions associated with driving in traffic on metro area highways and streets, providing the highest exposure conditions to benzene (Davis et al 2007). Concerning the other high-risk industrial sectors of ''Manufacture of mechanic machinery'' and ''Sale, maintenance and repair of motor vehicles; retail sale of automotive fuel'', comparable findings have Numbertof measures 5,000 -10,000 (1) 2,500 -5,000 (2) 0 -2,500 (1) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The breakthrough time was defined as the time that marked an increase of the baseline in the frontal chromatogram. The breakthrough volume V T g (cm 3 g À1 ) was calculated as the net retention volume of the target compound adsorbed per gram of adsorbent at the specific temperature. The pressure correction factor was not applied in the experiments.…”
Section: Breakthrough Characteristicmentioning
confidence: 99%
“…[1][2][3] Since the concentration of VOCs in air normally exists at the ppb or sub-ppb (v/v) levels, a preconcentration step is required to meet the detection limits of most modern gas chromatography (GC) detection methods. Adsorptive enrichment on solid adsorbents followed by thermal desorption is a well-established sample preparation technique, and is widely used for this purpose.…”
Section: Introductionmentioning
confidence: 99%